2021
DOI: 10.1111/jbg.12661
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of breeding value and accuracy using pedigree and genotype of Hanwoo cows (Korean cattle)

Abstract: The genetic improvement of Hanwoo is dependent on the estimated breeding value (EBV) of pedigree‐based Korean proven bull's number, and the genetic evaluation for cows is difficult due to insufficient pedigree and test records. Genomic selection involves utilizing the individual's genotype to estimate the breeding value (BV) and is determined to be an appropriate evaluation method for cows who lack test information. This study used pedigree and genotype to estimate and analyse BV and accuracy of Hanwoo cows in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…The higher accuracy for CWT, EMA, BF, and MS were determined to be 0.779, 0.758, 0.766, and 0.791 by Kim et al (2022), which is nearly identical to our Hanwoo reference findings. They also used the GBLUP approach on 919 Hanwoo cows to evaluate the prediction accuracy.…”
Section: Resultssupporting
confidence: 89%
“…The higher accuracy for CWT, EMA, BF, and MS were determined to be 0.779, 0.758, 0.766, and 0.791 by Kim et al (2022), which is nearly identical to our Hanwoo reference findings. They also used the GBLUP approach on 919 Hanwoo cows to evaluate the prediction accuracy.…”
Section: Resultssupporting
confidence: 89%
“…Many studies have shown that the GBLUP method is superior to PBLUP, and Naserkheil et al [ 26 ] reported that GBLUP (single- and multiple-trait GBLUP) was approximately 19% and 36% more accurate than conventional BLUP models (single- and multiple-trait GBLUP) for carcass traits in Hanwoo. Moreover, GBLUP has performed well in many studies, and the data of the present study showed similar trends [ 27 , 28 ].…”
Section: Resultssupporting
confidence: 83%
“…The effects of the locus for BayesRR follow multiple normal distributions. The hypothetical distribution of all the effects of the marker in each Bayesian method and the formula of effect distribution are shown in Table 1 ( 6 , 23–25 ). In this study, the model of Bayes methods is as follows ( Eq.…”
Section: Methodsmentioning
confidence: 99%
“…It had been reported that genomic selection has significant advantages in traits with low habitability and which are difficult to measure (5). It was confirmed that genomic selection can improve the accuracy of estimated breeding values, increase genetic progress, and reduce breeding costs (6)(7)(8). The factors that affect the accuracy of genomic selection include methods (9), reference population size (10), heritability (11), and marker density (12).…”
Section: Introductionmentioning
confidence: 94%